2021
DOI: 10.1016/j.jhazmat.2020.123788
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric ruthenium precursor as a photoactivated antimicrobial agent

Abstract: Ruthenium coordination compounds have demonstrated a promising anticancer and antibacterial activity, but their poor water solubility and low stability under physiological conditions may limit their therapeutic applications. Physical encapsulation or covalent conjugation with polymers may overcome these drawbacks, but generally involve multistep reactions and purification processes. In this work, the antibacterial activity of the polymeric precursor dicarbonyldichlororuthenium (II) [Ru(CO)2Cl2]n has been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…[5] Over the past few decades, the clinical treatment of S. aureus infections has become increasingly difficult, even antibiotic resistance is considered as a top global concern. [6][7][8] The most important cause of bacterial resistance is the overuse of antibiotics, which will accelerate the development of bacterial resistance. [9][10][11] In addition, the discovery of new antibiotics is not as fast as the spread of antibiotic resistance, resulting in the emergence of multiple drug-resistant strains, such as methicillin-resistant S. aureus and vancomycin-resistant S. aureus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Over the past few decades, the clinical treatment of S. aureus infections has become increasingly difficult, even antibiotic resistance is considered as a top global concern. [6][7][8] The most important cause of bacterial resistance is the overuse of antibiotics, which will accelerate the development of bacterial resistance. [9][10][11] In addition, the discovery of new antibiotics is not as fast as the spread of antibiotic resistance, resulting in the emergence of multiple drug-resistant strains, such as methicillin-resistant S. aureus and vancomycin-resistant S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Since the successful discovery of anti-tumor ability of cisplatin, other platinum family metal complexes have attracted extensive attention, especially ruthenium metal complexes with special chemical properties and obvious antibacterial activity and low cytotoxicity. [6,[21][22][23] It has been reported that ruthenium (II) metal complexes with polypyridine moieties have obvious antibacterial activity against gram-positive bacteria such as S. aureus. [24][25][26][27] And different ligands have various effects on the activity and cytotoxicity of ruthenium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their extremely small pore sizes (<1 nm), RO membranes provide an absolute barrier for microorganisms, keeping them in the water source and preventing waterborne diseases. 17 However, operating the RO process requires an external driving force such as electrical pumping to achieve the desired flow rate. 18,19 The requirements of a stable electricity supply and maintenance of RO water treatment systems increase the operation costs, making them impractical for use in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently years, transition metal-based compounds explored as antimicrobials or adjuvants to existing antibiotics were received widely attention (Frei et al, 2020;Pisani et al, 2010;Wareham et al, 2015). It worthy to noted that many ruthenium-based complexes have displayed significant antimicrobial activity (Ghosh et al, 2021;Jain et al, 2021;Li et al, 2015;Pandrala et al, 2013;Yang et al, 2018). Up to now, there exist over 200 scientific literatures on the antimicrobial activity of various ruthenium-based compounds.…”
Section: Introductionmentioning
confidence: 99%